Research progress on S-palmitoylation modification mediated by the ZDHHC family in glioblastoma - Tang, Beiyan; Kang, Wei; Dong, Qiang; Qin, Zhenwei; Duan, Lei; Zhao, Xianjun; Yuan, Guoqiang; Pan, Yawen (Frontiers in Cell and Developmental Biology, 2024)
S-Palmitoylation has been widely noticed and studied in a variety of diseases. Increasing evidence suggests that S-palmitoylation modification also plays a key role in Glioblastoma (GBM). The zDHHC family, as an important member of S-palmitoyltransferases, has received extensive attention for its function and mechanism in GBM which is one of the most common primary malignant tumors of the brain and has an adverse prognosis. This review focuses on the zDHHC family, essential S-palmitoyltransferases, and their involvement in GBM. By summarizing recent studies on zDHHC molecules in GBM, we highlight their significance in regulating critical processes such as cell proliferation, invasion, and apoptosis. Specifically, members of zDHHC3, zDHHC4, zDHHC5 and others affect key processes such as signal transduction and phenotypic transformation in GBM cells through different pathways, which in turn influence tumorigenesis and progression. This review systematically outlines the mechanism of zDHHC family-mediated S-palmitoylation modification in GBM, emphasizes its importance in the development of this disease, and provides potential targets and strategies for the treatment of GBM. It also offers theoretical foundations and insights for future research and clinical applications.